Factors affecting English pronunciation learning of ethnic minority students at Lai Chau Community College = Những nhân tố ảnh hưởng đến việc học phát âm Tiếng Anh của sinh viên dân tộc thiểu số ở trường Cao đẳng Cộng đồng Lai Châu. M.A Thesis - Phùng, Thị Thanh Nga (2019)
Pronunciation plays a very important part in learning English but it is a big problem for most of ethnic minority students at Lai Chau Community College, the only college in Lai Chau province where more than 90% of students are ethnic. Most of them have difficulties in English pronunciation learning. Until now, no research on English pronunciation learning of the ethnic learners at Lai Chau Community College has been carried out.